Global research landscape on active surveillance for papillary thyroid microcarcinoma: a bibliometric analysis - Dong-Shu Kang; Yu-Hao Lin; Jian-Qing Tian (Discover Oncology)
Abstract Background It has been proven that the active surveillance (AS) is safe and feasible for low-risk papillary thyroid microcarcinomas (PTMC). There has been no bibliometric assessment of the scientific advancements in this field. We conducted this study to determine the characteristics and trends of published research on AS for PTMC. Methods In this study, articles on AS for PTMC published between 2014 and 2024 were identified using the Web of Science Core Collection database. Bibliometric analysis and visualization were conducted using VOSviewer and CiteSpace. Results 277 publications from 39 countries were identified, demonstrating a growth trend between 2014 and 2024. The United States of America dominated with the highest number of published papers, followed closely by South Korea and Japan. The most significant journal was *Thyroid*, and the leading author was Akira Miyauchi. Kuma Hospital and Memorial Sloan Kettering Cancer Center emerged as leading institutions. Keyword analysis revealed that, alongside the title-related terms of this study, “management,” “quality of life,” “lymph node metastasis,” “progression,” and “association guidelines” formed the core keywords in this field. Conclusion Active surveillance for low-risk PTMC has been endorsed and recommended by researchers in numerous countries. This study identified the current most active frontiers in this field and focused on candidate population profiling, tumor progression evaluation, cost-effectiveness of the active surveillance (AS) approach, and quality of life assessment for patients. This paper summarizes the controversial issues and provides a reference direction for researchers seeking to explore novel approaches in this field.